Investigating Academic Writing: Exploring English Department Students’ Perceptions of Challenges - Habi Sabda Ihsan; Musdizal (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Academic writing is a crucial component of university education, yet it remains one of the most challenging skills for EFL students. This study investigates the perceptions of English Department students at IAIN Kerinci regarding the challenges they face in academic writing. Using a mixed-method approach, the research involved four undergraduate students who had completed academic writing courses in previous semesters. Data were collected through writing performance tests and semi-structured interviews. The quantitative findings indicate that students performed well in content (average score: 7.5) but struggled significantly with writing coherence (4.5). Vocabulary and grammar showed standard capability (6.875 and 6.25). The qualitative results revealed deeper challenges, including difficulties in constructing coherent paragraphs, selecting appropriate vocabulary, applying complex grammar structures, and managing writing anxiety. Contributing factors included lack of motivation, limited reading habits, and insufficient exposure to academic texts. Furthermore, students emphasized the importance of feedback from lecturers and self-reflection as key strategies for development. The findings suggest that while students may be confident in generating ideas, they require more support in expressing those ideas effectively through structured, cohesive academic writing. This study contributes to the field by highlighting the need for integrating linguistic, motivational, and strategic instruction in EFL academic writing contexts.